PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IVA SDN 016 BUKIT TIMAH - Susanti, Epi Susanti; Witri, Gustimal Witri; Marhadi, Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research based is the low result of grade learning mathematics SDN 016 Bukit Timah class IVA that still low with an average value is 67,17. Minimum Completeness Criteria (MCC) of mathematic studies is 75. The student in the class 23 people, only 7 students who achieve MCC, with completeness classical is 30,43%. This research is an Classroom Action Research (CAR) which aims to improve the students’ achievement of mathematic studies in SDN 016 Bukit Timah class IVA by implementing cooperative learning type Student Team Achievement Division (STAD). The formulation of this research: “Is the implementing of cooperative learning type STAD can increase students’ achievement of mathematic studies in SDN 016 Bukit Timah class IVA?” This research was done on March 26, 2014 to April 10, 2014 by 2 cycles. The subjects were students , SDN 016 Bukit Timah class IVA totalling 23 people who use as data source. The instrument of this research are teacher and students activities sheets and students achievement. This thesis presents percentage of teacher activities in first meeting of cycle I is 66,6% and second meeting of cycle I increased to 83,3%, in first meeting of cycle II is 91,6% and second meeting of cycle II increased to 95,8%. Percentage of students activities in first meeting of cycle I is 62,5% and second meeting of cycle I increased to 75%, in first meeting of cycle II is 87% and second meeting of cycle II increased to 91,6%. The average value of students’ achievement before an action was 67,17. After the action was giving, the average of students’ achievement in cicle I increased to 74,13 and in cycle II increased to 80,21. Based on research value in SDN  016 Bukit Timah class IVA , it is known that hypothesis action was accepted. It can be concluded that the implementing of cooperative learning type Student Time Achievement Division (STAD) can increase students’ achievement of mathemtics studies in  SDN 016 Bukit Timah class IVA Key Words : Cooperative Learning Type STAD,  Achievement of mathematics.